2017
DOI: 10.1101/167692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Termite communities along a disturbance gradient in a West African savanna

Abstract: Termites are important ecosystem engineers, crucial for the maintenance of tropical biodiversity and ecosystem functioning. But they are also pests which cause billions of dollars in damage annually to humans. Currently, our understanding of the mechanisms influencing species occurrences is limited and we do not know what distinguishes pest from non-pest species. We analyzed how anthropogenic disturbance (agriculture) affects species occurrences. We tested the hypothesis that strong disturbance functions as a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Meanwhile, several studies have shown that termites are sensitive to habitat disturbance (e.g. Eggleton et al 2002;Sanabria et al 2016;Schyra and Korb 2019). Wide-scale agricultural intensification and monoculture system in an oil palm plantation is presumed to be the primary factor that causes biodiversity decline and disturbs the ecological balance (Wood 1971;Vijay et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several studies have shown that termites are sensitive to habitat disturbance (e.g. Eggleton et al 2002;Sanabria et al 2016;Schyra and Korb 2019). Wide-scale agricultural intensification and monoculture system in an oil palm plantation is presumed to be the primary factor that causes biodiversity decline and disturbs the ecological balance (Wood 1971;Vijay et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our conclusions are supported by several studies, which all showed that soil feeders are especially rich under warm, humid conditions (Bourguignon et al., ; Couto et al., ; Eggleton et al., ; Eggleton et al., ; Eggleton, Davies et al., ; Eggleton, Bignell et al., ; Isra et al., ; Palin et al., ; Roisin et al., ; Valladares, ). For instance, they decline when comparing forests with neighboring savannahs in Africa (Crolaud, Souleymane, & Yao, ; Dosso et al., ; Hausberger & Korb, ; Schyra & Korb, ), or along anthropogenic disturbance gradients where forests are turned into more open areas (Attignon et al., ; Hausberger et al., ; Trabi, Soro, Yeboue, Honate, & Tano, ). Along with this decline of soil feeders, total termite richness drops (Alves et al., ; Genet et al., ; Houston, Wormington, & Black, ; Muvengwi, Mbiba, Ndagurwa, Nyamadzawo, & Nhokovedzo, ; Viana et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological studies on termites have been surveys to determine species richness and community composition in rain forests, savanna, and disturbed areas (e.g., Ackerman et al., ; Bignell & Eggleton, ; Bourguignon et al., ; Dahlsjö, Parr, Malhi, Meir, & Eggleton, ; Davies, Eggleton, Jones, Gathorne‐Hardy, & Hernández, ; for savanna: Ferrar, ; Schyra & Korb, ; Wood, Johnson, Bacchus, Shittu, & Anderson, ; for disturbed and fragmented forests: Eggleton, ; Eggleton et al., ; Jones et al., ; Roisin & Leponce, ; Sena, Vasconcellos, Gusmão, & Bandeira, ; Vasconcellos et al., ; for cultivated areas: Attignon, Lachat, Sinsin, Nagel, & Peveling, ; Coaton, ; Dosso, Deligne, Yeó, Konate, & Linsenmair, ; Leponce, Roisin, & Pasteels, ; Luke, Fayle, Eggleton, Turner, & Davies, ). However, termite diversity in tropical dry forests has rarely been studied (Eggleton, ; Jones & Eggleton, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a savannah ecosystem, we investigated termite assemblages in the relatively natural Oti-Kéran National Park (West Africa; 10°17’ to 10°08’ N; 0°28’ to 0°51’ E; Fig 1) in Togo, and compared these assemblages communities with those from a previous study of anthropogenically disturbed habitats (fallows) in the same region [13]. Permissions for the field work were issued by the ‘ Ministere de l’Environement et des Ressources Forestieres , Direction Generale de l‘Odef’ , Lomé, Togo.…”
Section: Methodsmentioning
confidence: 99%
“…To test these hypotheses, we first identified all species occurring in the different assemblages using morphological and molecular markers [13]. A molecular approach using sequence data is necessary to unambiguously identify all termite samples as morphology markers are not sufficient [14, 15].…”
Section: Introductionmentioning
confidence: 99%